A case report of psoriasis flare following immunotherapy: Report of an important entity and literature review. (January 2020) - Politi, Anastasia; Angelos, Dimas; Mauri, Davide; Zarkavelis, George; Pentheroudakis, George
Immune checkpoint inhibitors, such as anti-cytotoxic T-lymphocyte–associated antigen-4 and anti-programmed death-1, are a type of cancer immunotherapy approved for late-stage malignancy treatment. However, such therapies often induce immune-related adverse events. During anti-programmed death-1 blockade therapy, the most commonly reported adverse effects are skin toxicities, such as psoriasis—a chronic immune-mediated inflammatory disorder affecting the skin. We present the clinical characteristics of flared psoriasis in one patient under anti-programmed death-1 therapy who was diagnosed with T2N2M0/IIIB squamous lung carcinoma with a history of psoriasis for the past 5 years, exacerbated after the first cycle of nivolumab. After the third cycle, the extensive skin plaques necessitated treatment cessation. Following the discontinuation of anti-programmed death-1 treatment, skin lesions were treated locally. Possibly, anti-programmed death-1 immunotherapy can trigger immune-mediated diseases, such as psoriasis. Physicians should be alert to immune-related adverse events. Continuation or permanent cessation of treatment depends on the severity and reversibility of immune-related adverse events.